Dictionary of the sport and exercise sciences - Anshel, Mark H. (Mark Howard); Freedson, Patty 1953-; Hamill, Joseph; Haywood, Kathleen; Horvat, Michael; Plowman, Sharon A. (Human Kinetics Books, 1991)
Dictionary intended for professionals and students of various disciplines involved in the exercise and sport sciences, e.g., biomechanics, exercise physiology, and sport psychology. Excludes dance, physical education, research, design, statistics, sports medicine, and specific sports. Entries give word or phrase and brief, explanatory definition.Cross references